2008
DOI: 10.1590/s1516-35982008000500010
|View full text |Cite
|
Sign up to set email alerts
|

Farelo de trigo e complexo enzimático na alimentação de poedeiras semipesadas na fase de produção

Abstract: RESUMO -O estudo foi conduzido com o objetivo de avaliar os efeitos da inclusão de farelo de trigo (FT) na ração com ou sem a suplementação de um complexo enzimático (CE) sobre o desempenho e a produção de ovos de frangas semipesadas na fase de produção. Foram utilizadas 288 frangas Lohmann Brown, distribuídas em delineamento inteiramente casualizado, em esquema fatorial 4 × 2, composto de quatro níveis de farelo de trigo (0, 3, 6 e 9%) na ração e da suplementação de complexo enzimático (0 ou 100 g/100 kg de r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
1
8
0
4
Order By: Relevance
“…The lack of effect on feed intake of birds fed diet with soybean hulls and coffee husks in comparison with those fed diet containing wheat bran indicates that the changes caused by the composition of such fiber sources in the viscosity of gastrointestinal contents probably were not significant enough to compromise feed intake. Those results agree with Araujo et al (2008), who observed that the inclusion of up to 9% wheat bran in the feed did not interfere with its intake. According to the authors, the physiological maturity of the gastrointestinal tract of animals is an important factor to be observed in adjusting the levels of alternative feeds in diets to digestive capacity of layers, especially the low digestibility of the nutrients in these feeds.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of effect on feed intake of birds fed diet with soybean hulls and coffee husks in comparison with those fed diet containing wheat bran indicates that the changes caused by the composition of such fiber sources in the viscosity of gastrointestinal contents probably were not significant enough to compromise feed intake. Those results agree with Araujo et al (2008), who observed that the inclusion of up to 9% wheat bran in the feed did not interfere with its intake. According to the authors, the physiological maturity of the gastrointestinal tract of animals is an important factor to be observed in adjusting the levels of alternative feeds in diets to digestive capacity of layers, especially the low digestibility of the nutrients in these feeds.…”
Section: Discussionsupporting
confidence: 92%
“…The Ciênc. Agrotec., Lavras, v.38, n.6, p.573-580, nov./dez., 2014 specific gravity was determined according to the method implemented by Araujo et al, (2008).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, associating nutritional management with reproductive performance, several nutrients are important for sperm production, with lipids presenting remarkable functions integrated to energy metabolism and essential cellular components of biological membranes (Araújo, 2008;Makker, Agarwal, & Sharma, 2009). …”
Section: Introductionmentioning
confidence: 99%